African relapsing fever borreliae genomospecies revealed by comparative genomics - Haitham eElbir; Laurent eAbi-Rached; Pierre ePontarotti; Niayz eYoosuf; Michel eDRANCOURT (Frontiers Media S.A., 2014)
Background: Relapsing fever borreliae are vector-borne bacteria responsible for febrile infection in humans in North America, Africa, Asia and in the Iberian Peninsula in Europe. Relapsing fever borreliae are phylogenetically closely related, yet they differ in pathogenicity and vectors. Their long-term taxonomy, based on geography and vector grouping, needs a re-appraisal in the genomic area. We therefore embarked into genomic analyses of relapsing fever borreliae, focusing on species found in Africa. Results: Genome-wide phylogenetic analyses group Old World Borrelia crocidurae, Borrelia hispanica, B. duttonii and B. recurrentis in one clade, and New World Borrelia turicatae and Borrelia hermsii in a second clade. Accordingly, average nucleotide identity is 99% among B. duttonii, B. recurrentis and B. crocidurae and 96% between latter borreliae and B. hispanica while the similarity is 86% between Old World and New World borreliae. Comparative genomics indicates that the Old World relapsing fever B. duttonii, B. recurrentis, B. crocidurae and B. hispanica have a 2,514-gene pan-genome and a 933-gene core genome that includes 788 chromosomal and 145 plasmidic genes. Analysing the role that natural selection has played in the evolution of Old World borreliae species revealed that 55 loci were under positive diversifying selection, including loci coding for membrane, flagellar and chemotaxis proteins, three categories associated with adaption to specific niches. Conclusions: Genomic analyses led to a reappraisal of the taxonomy of relapsing fever borreliae in Africa. These analyses suggest that B. crocidurae, B. duttonii and B. recurrentis are ecotypes of a unique genomospecies, while B. hispanica is a distinct species.